1992
DOI: 10.1128/iai.60.6.2493-2499.1992
|View full text |Cite
|
Sign up to set email alerts
|

Role of specific determinants in mannan of Candida albicans serotype A in adherence to human buccal epithelial cells

Abstract: Candida albicans serotype A (C. albicans A) possesses a specific antigen, designated antigen 6, which resides in mannans on the cell surface. To determine the role of the mannan moiety of the C. albicans cell wall in adherence to buccal epithelial cells, we used antigen 6-deficient mutants which had been isolated by screening with an agglutinating monoclonal antibody against antigen 6 (MAb-6). 'H nuclear magnetic resonance spectral analysis of the purified mannans from the mutants showed a loss of the signals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(36 citation statements)
references
References 37 publications
1
34
1
Order By: Relevance
“…Because the b-1,2-linked mannose unit is present among the pathogenic fungi only in the mannan of the genus Candida and the b-1,2 linkage-containing side chains behave as strong antigens, many workers [18][19][20][21][22][23][24][25] have produced monoclonal antibodies to b-1,2-linked mannose units to protect against candidiasis, for the serodiagnosis of candidiasis, or for the identification of mechanisms of Candida infection. Furthermore, studies have indicated the b-1,2-linked mannose units participate in the adherence of Candida cells to mammalian cells as the first step in infection [26][27][28]. Poulain and his coworkers [29][30][31][32] reported that the b-1,2 linkage-containing oligosaccharides and phospholipomannans induce cytokine production and may act as a virulent factor in candidiasis.…”
mentioning
confidence: 99%
“…Because the b-1,2-linked mannose unit is present among the pathogenic fungi only in the mannan of the genus Candida and the b-1,2 linkage-containing side chains behave as strong antigens, many workers [18][19][20][21][22][23][24][25] have produced monoclonal antibodies to b-1,2-linked mannose units to protect against candidiasis, for the serodiagnosis of candidiasis, or for the identification of mechanisms of Candida infection. Furthermore, studies have indicated the b-1,2-linked mannose units participate in the adherence of Candida cells to mammalian cells as the first step in infection [26][27][28]. Poulain and his coworkers [29][30][31][32] reported that the b-1,2 linkage-containing oligosaccharides and phospholipomannans induce cytokine production and may act as a virulent factor in candidiasis.…”
mentioning
confidence: 99%
“…1 Although the infections were mainly reported in Australia, Africa, North America, Europe and Thailand, 1,2 few reports including a cutaneous infection have been reported in Japan. 3 We report a case of N. transvalensis mycetoma on the left arm of a healthy male, with repeated recurrences for 25 years without visceral metastasis.…”
Section: Supporting Informationmentioning
confidence: 93%
“…With regard to the interaction between keratinocytes and C. albicans, mannan adhesion is possibly involved in the adhesion mechanism. 3 However, secreted aspartic proteinases (SAPs), one of the major virulence attributes of C. albicans, should be considered as another factor in their interaction. 4 Further explorations using neutralizing antibodies against antigen 6, mannan and SAPs should be made to shed light on this problem.…”
Section: (A) (B) (C)mentioning
confidence: 99%
“…N-acetylgluc?samine, mannosamine, glucosamine and galactosamine (Collins-Lech et al, 1984;Critchley and Douglas, 1987b). Also, a number of putative adhesins of C. albicans have been studied including cell wall chitin (Segal et al, 1982;Lehrer et al, 1988) lipids (Ghannoum et al, 1986), complement receptors (Gilmore et al, 1987;Alaei et al, 199~), fibronectin adhesins (Klotz et al, 1994), mannan (Sandin, 1987;Miyakawa et al, 1992), proteins (Calderone and ScheId, 1987;Critchley and Douglas, 1987a), and mannoproteins (Tosh and Douglas, 1992;I,?bert-Bernard et .al, 1995). Evidence suggests that C. albl~ans rnannoprotems are the principle adhesins responsible for a~hcslOn to host cells and these have been partially characterised (Tosh and C. albicans…”
Section: Adherencementioning
confidence: 99%